Getting meanings across: A case study of a bilingual child / Gan Geok Choo - Gan, Geok Choo (2015)
From the time of fertilisation, a human baby grows and develops in a complex manner. In the uterus, a baby feels, hears, sees, tastes, learns, remembers and communicates with his/ her mother (Stoppard, 1996). Subsequently, the baby will undergo several milestones in his/ her life. The communication ‘deficits’ of children with autism and minimal or no speech have been the main focus of much research in the past especially in the western countries (Potter & Whittaker, 2001; Collard and HubPages pp : 75). In Malaysia, Kow (2000) has done a research on child language entitled ‘Strategies employed by pre-school children in communicating meaning’. In order to establish a 2- way communication, this study will look into how a five-year old bilingual child gets his meanings across in various settings and thus to find out what the communication strategies are. A pilot study was carried out and it showed that the participant of this study invented new creative communication strategies namely ‘spelling’ and ‘singing’ in order to get his meanings across. In this study, data will be collected through close participant observation by using qualitative approach. As the researcher is also a member of the study, focus is given to the child in the home setting and occasionally outside the home setting. The period of observation took up seven months. Data were collected from June 2009 until December 2009. The participant of this study was given the opportunity to draw and colour drawings of his kindergarten’s peers and to later describe them. Data were collected using pen and paper method, video-camcorder and tape recording. Data were then transcribed using adapted ‘Jeffersonian Transcript Notation’. All utterances that contained non-English words were translated. At the beginning of data collection, JH was only four years old. At present, he is five years old. He converses in Hokkien and English. He is the only child in a middle class family. Both parents speak Hokkien and English but use only English with him. He attends an English medium kindergarten and is cared for by his maternal grandaunt who speaks Hokkien with him. The findings of this study can benefit teachers, writers for educational television programmes and curriculum designers for they can incorporate better and more effective teaching materials to facilitate learning so that bilingual children can learn to be more confident when they employ spelling and singing communication strategies to communicate with other people. There are several limitations in this study. This is just one case study hence the data collected might not be sufficient and is not meant to be representative of a justified research on the communication strategies adopted by a five-year old simultaneous bilingual child in general. Furthermore, due to the uniqueness of every human being, even for identical twins, a bigger collection of data at random from various simultaneous bilingual children in both genders, of Chinese or any other races definitely can contribute to more accurate and generalized findings.